Fattening heifers for the fall market. - Smith, E.F.; Good, D.L.; Cox, R.F.; Mackintosh, D.L. (Kansas Agricultural Experiment Station, 2012)
The purpose of this experiment is to develop a desirable system of fattening heifer calves similar to the deferred full-feeding system for steer calves. The system developed for good quality steer calves consists of three phases: (1) producing 225-250 pounds of gain during the winter, which usually requires the feeding of four to five pounds of grain per head daily; (2) grazing 90 days without grain; (3) full-feeding 100 days in the dry lot.
Keywords: Beef; Bluestem pasture; Gain; Grain